Perceptions of junior high school science teachers in the implementation of the independent curriculum: A qualitative study in South Dampal District, Toli-Toli Regency - Eviyani Eviyani; Ahmad Akramullah (Privietlab, 2026)
The Merdeka Curriculum is the latest educational curriculum implemented in Indonesia to improve learning outcomes. This study aims to describe the perceptions of junior high school science teachers regarding the implementation of the Merdeka Curriculum: a qualitative study in South Dampal District, Toli-Toli Regency. The method used in this study was descriptive and qualitative. The research instruments used questionnaires and interviews, and the data collection techniques included questionnaires, interviews, and documentation. The data were analyzed descriptively. The results show that junior high school science teachers' perceptions of the Merdeka Curriculum in South Dampal District are generally positive. This is demonstrated by indicators of absorption of external stimuli (80%), understanding (80%), assessment, and evaluation (80%). These findings indicate that teachers have a fairly good understanding of the concept, objectives, and implementation of the Merdeka Curriculum. With this understanding, teachers can implement the Merdeka Curriculum more effectively in the learning process, thereby improving the quality of education in junior high schools in South Dampal District. In addition, teachers from schools that have implemented the Independent Curriculum and those that have not fully implemented it showed positive perceptions.